2016
DOI: 10.17795/ijep34692
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Lactobacillus Isolated From Kashk-e Zard and Tarkhineh, Two Iranian Traditional Fermented Foods

Abstract: Background: Nowadays, microbial food safety is an increasing public health concern worldwide, especially in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…All strains showed strong to moderate antimicrobial activity against S. aureus, Salmonella Typhimurium and E. coli. L. acidophilus, L. plantarum and L. rhamnosus showed moderate antimicrobial activity against E. coli while other researchers reported a relatively higher antimicrobial activity of Lactobacillus species against E. coli [41]. Our results are in comparison with the finding, which showed moderate activity against Salmonella species [35].…”
Section: Discussionsupporting
confidence: 63%
“…All strains showed strong to moderate antimicrobial activity against S. aureus, Salmonella Typhimurium and E. coli. L. acidophilus, L. plantarum and L. rhamnosus showed moderate antimicrobial activity against E. coli while other researchers reported a relatively higher antimicrobial activity of Lactobacillus species against E. coli [41]. Our results are in comparison with the finding, which showed moderate activity against Salmonella species [35].…”
Section: Discussionsupporting
confidence: 63%
“…The Lactobacillus isolates ( L. plantarum , L. fermentum and L. salivarius ) from fermented fruits and vegetables had broad antibacterial spectrum (ZDI: 26–28 mm), against food-borne bacterial pathogens, as has been reported by Manzoor et al [ 40 ]. A large number of lactobacilli isolates, including L. acidophilus , L. plantarum and L. rhamnosus , procured from traditional fermented foods prepared with the combination of cereal and dairy materials, had excellent antibacterial activity against E. coli with ZDIs 17–20, 21–30, 14–31 mm, respectively [ 10 ].The probiotic Lactobacillus strains: L. fermentum , L. casei and L. acidophilus , isolated from buffalo milk showed growth inhibitory activity against Vibrio cholerae , S. typhi , E. coli , and Shigella species having ZDIs 10–22 mm [ 36 ]. The lactobacilli strains, including L. rhamnosus and L. plantarum , procured from dairy food products (commercially available yoghurt and cheese) and rumen contents of cow did not show growth inhibitory activity against E. coli , while Salmonella menston was found sensitive to all the test lactobacilli, as per the demonstration of Jose et al [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the Lactobacillus plantarum isolates could protect the infection caused with Salmonella typhi through interference with growth as well as virulence properties (adherence, invasion, and cytotoxicity) of the pathogen [ 7 ]. A large number of lactobacilli isolates, procured from traditional fermented foods prepared with the combination of cereals and dairy materials, including L. acidophilus , L. plantarum and L. rhamnosus had excellent antibacterial activity against Escherichia coli ATCC 700728 standard strain [ 10 ]. The lactic acid bacterial strains L. acidophilus , L. plantarum , L. fermentum , L. casei and L. rhamnosus , can effectively be applied against the urinary tract infection causing Proteus species ( P. mirabilis and P. vulgaris ), as has been reported by Goudarzi et al [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The probiotic Lactobacillus strains: L. fermentum, L. casei and L. acidophilus, isolated from buffalo milk showed growth inhibitory activity against Vibrio cholerae, S. typhi, E. coli, and Shigella species having ZDIs 10-22 mm (Rahman et al, 2015). Many lactobacilli isolates, including L. plantarum obtained from traditional fermented foods prepared with the combination of cereal and dairy materials, had an excellent antibacterial activity against E. coli with ZDIs 20 mm (Mashak et al, 2016).…”
Section: Discussionmentioning
confidence: 99%